Mesenchymal Stem Cells as Therapeutics Agents: Quality and Environmental Regulatory Aspects - Patricia Galvez-Martin; Roger Sabata; Josep Verges; José L. Zugaza; Adolfina Ruiz; Beatriz Clares (Stem Cells International)
Mesenchymal stem cells (MSCs) are one of the main stem cells that have been used for advanced therapies and regenerative medicine. To carry out the translational clinical application of MSCs, their manufacturing and administration in human must be controlled; therefore they should be considered as medicine: stem cell-based medicinal products (SCMPs). The development of MSCs as SCMPs represents complicated therapeutics due to their extreme complex nature and rigorous regulatory oversights. The manufacturing process of MSCs needs to be addressed in clean environments in compliance with requirements of Good Manufacturing Practice (GMP). Facilities should maintain these GMP conditions according to international and national medicinal regulatory frameworks that introduce a number of specifications in order to produce MSCs as safe SCMPs. One of these important and complex requirements is the environmental monitoring. Although a number of environmental requirements are clearly defined, some others are provided as recommendations. In this review we aim to outline the current issues with regard to international guidelines which impact environmental monitoring in cleanrooms and clean areas for the manufacturing of MSCs.